Improving adhesion between aramid fibers and natural rubber through morphological and synthetic modification of the fibers. Issue 24 (27th July 2017) - Kanbargi, Nihal; Lesser, Alan J.
ABSTRACT: In this article, we present new methods to improve the adhesion between poly(paraphenylene terephthalamide) fibers and a natural rubber for tire reinforcement. Fiber pretreatments are applied to create new surface morphologies on the fiber that enables enhanced adhesion between the fiber and rubber matrix. The pretreated fibers are then subject to treatments with coupling agents in the presence of supercritical carbon dioxide (scCO2 ) in an attempt to permeate the fiber surface and chemically bind the fiber to the rubber matrix. Shear lag analysis using a Kelly Tyson approach is compared to more refined models to evaluate optimum test parameters for fiber pull‐out adhesion tests. The results show that the adhesion increases by approximately 100% when compared to conventional composites. Failure analysis of fiber surface reveals a suppression of interfacial failure. The effects of pretreatments on fiber properties are also characterized, and the optimization between fiber properties, fiber–matrix interface properties, and overall composite properties are discussed. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45520. Abstract :